Analisis amilase serum pre dan post-endoscopic cholangiopancreatography pada penderita kanker pankreas tahun 2017-2018 di RSUP Dr. Wahidin Sudirohusodo, Makassar, Indonesia - Nunung Meisari Indah Umar; Nurahmi Nurahmi; Ruland DN Pakasi (Intisari Sains Medis, 2019)
Background: Pancreatic cancer is a cancer of the thirteenth sequence of events worldwide and the fourth most common cause of death by some cancers. Amylase levels can increase if there is damage to pancreatic cells. Therapeutic ERCP procedure is expected to reduce amylase levels that are elevated in pancreatic cancer. This study aimed to evaluate the preand post ERCP serum amylase in pancreatic cancer patients.Method: Observational retrospective using data from pancreatic cancer patients in January 2017 - January 2018 at the Laboratory of Clinical Medicine and Mechanical Installation of Dr. Wahidin Sudirohusodo Hospital, Makassar. Data were analysed using SPSS version 22 software for windows.Results: Total of 39 pancreatic cancer subject aging 31–93 years were found, most of them were women. PreERCP amylase levels with a value of 167.5 ± 235.6 as against of 137.5 ± 159.4 in post ERCP. Some subject showed a decreased level and some showed an increased level. Statistical tests did not show significant results (Wilcoxon-signed rank test p> 0.05).Conclusion: Serum amylase levels that have increased therapeutic post ERCP can be information for clinicians to pay more attention to ERCP cannulation techniques in order to avoid post ERCP complications.